Pembinaan Keagamaan melalui Islamic Storytelling di Desa Sudirman, Kecamatan Tanralili, Kabupaten Maros: Religious Guidance through Islamic Storytelling in Sudirman Village, Tanralili Subdistrict, Maros Regency - Andi Dahmayanti; Abdurrahman, Armida; Risdayani, Risdayani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The present Community Service Programme focuses on the implementation of Islamic Storytelling, conducted by STIBA Makassar's Kuliah Kerja Nyata (KKN) VII students in Sudirman Village, Tanralili District, Maros Regency.The objective of the programme is twofold: firstly, to increase the understanding and knowledge of religious values in children through exemplary stories of prophets and companions; and secondly, to evaluate children's responses and participation in the religious learning process. The method of implementing this programme consists of the following stages: first, a preparatory stage which includes the preparation of Islamic story materials and facilitator training; second, implementation through regular Islamic Storytelling sessions with question and answer techniques and discussions; and third, evaluation of the effectiveness of the methods used. The results showed that the programme succeeded in improving children's understanding of religious values such as honesty, patience, and sacrifice, as well as developing their religious character. The practical implementation of the programme has been shown to have a positive impact on children's participation and understanding through active interaction, thus contributing to the formation of a noble generation and the strengthening of religious understanding in the community. Islamic Storytelling has been demonstrated to make a positive contribution to religious development in Sudirman Village.